Potensi Daya Hambat Filtrat Zat Metabolit Actinomycetes dari Kebun Raya Bogor terhadap Pertumbuhan Candida albicans dan Malassezia furfur - Venita Octavia Tambunan; Meiskha Bahar; Andri Pramono; Cut Fauziah; Hany Yusmaini; Fajriati Zulfa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Candida albicans and Malassezia furfur are types of fungi that often cause infections in humans. Widespread fungal infections and lack of therapeutic options can develop fungal resistance and become serious problems in the future. Actinomycetes are Gram-positive bacteria that can produce secondary metabolites such as antifungal, antibacterial, and anticancer. The study aimed to determine the effectiveness of the metabolite filtrate Actinomycetes as an antifungal agent against the in vitro growth of C.albicans and M. furfur. This type of research is a laboratory experimental study with a post-test group design only using metabolite concentrations Actinomycetes of 25%, 50%, 75%, 100%, antifungal testing is done using the agar diffusion method on Sabouraud Dextrose Agar Media. Of the four concentrations, the average diameter of the clear zone for C.albicans is 11.65mm; 12.48mm; 13.63mm and 13.80mm and for M.furfur is 6,025mm; 8,05mm; 9,1mm and 9,9mm. There was a significant difference between each treatment group with a p-value of < 0.05. The compound Metabolite filtrate Actinomycetes derived from Actinomycetes can potentially be antifungal with one of its mechanisms binding to ergosterol in the cell wall that will interfere with the integrity of the fungal cell wall.